ICTs and new scenarios for diversity - Tomé, José Manuel Salum (Seven Editora, 2023)
Research is a process aimed at seeking new knowledge, in this case, it will be to find alternative paths in the field of new technologies that serve to support special educational needs. Society demands these technological contributions to solve problems that contribute to inclusion, which led man to work with greater ergonomics; The school, a social institution, also needs these resources so that all students can build a teaching process of functional and meaningful learning for every student. The educational system outlines an education that attends to the educational needs of all students, and from these pages, the intention is that new technologies are a path of support that assists diversity and inclusion. DOI: https://doi.org/10.56238/devopinterscie-021